PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, BUDAYA ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SEKOLAH DASAR NEGERI DI DISTRIK DRAMAGA, KABUPATEN BOGOR - Dadan Dadan; Yulita Pujilestari; Ruknan Ruknan (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of principal leadership, organizational culture, and work motivation on teacher performance at public elementary schools in Dramaga District, Bogor Regency. The research employed a quantitative approach using a survey method. The population consisted of all public elementary school teachers in Dramaga District, with a total sample of 180 teachers selected through proportional sampling techniques. Data were collected using Likert-scale questionnaires that had been tested for validity and reliability, and subsequently analyzed using simple and multiple linear regression with the assistance of IBM SPSS Statistics version 23. The results indicate that principal leadership, organizational culture, and work motivation each have a positive and significant effect on teacher performance, both partially and simultaneously. Organizational culture was identified as the most dominant variable influencing teacher performance. These findings suggest that teacher performance is not determined by a single factor, but rather by the synergy of effective school leadership, a supportive organizational culture, and high levels of work motivation. The implications of this study highlight the importance of strengthening principal leadership practices, fostering a conducive school culture, and enhancing teacher motivation in order to improve teacher performance sustainably.